Pengembangan Bahan Ajar E-Book Berbasis Kontekstual Pada Mata Pelajaran Praktikum Akuntansi Lembaga Kelas XI SMK - Firda Sukma Hardini; Susanti Susanti (Jurnal Pendidikan Akuntansi (JPAK), 2020)
The increasingly rapid and modern development of science and technology brings a new paradigm in human life in all aspects. The educional world does not desert from the use of technology in the learning process. Along with curriculum charges occurs in Indonesia, which are in line with the development of learning tools, namely one of the teaching materials. The aim of this development research is to make the available e-books more perfect by developing electronic teaching materials based on a contextual approach for class XI SMK second semester accounting practicum subjects/government agencies. The 4D model was chosen by the researchers because this model was systematically arranged to solve problems in learning and adapted to the needs of students. The researcher only carried out the stages of determining, designing, and developing because the researcher focused on producing contextual-based learning materials, testing the feasibility of the book to be used in the learning process. To be carried out, a study and trial was carried out by three experts from various majors and a trial was carried out on 20 students. Based on these results, the criteria were "very feasible" to be used and students were able to understand the material presented.